Sondagem das anáforas não correferenciais ativadas em processos interpretativos de fábulas. - Reis, Leidiani da Silva (2012)
Given the difficulty of students to interpret a text, this research aims at providing some reflections on the interpretive process in the teaching of Portuguese. Specifically, we discuss the importance of linguistic elements in text interpretation. Among the various language resources, this study addresses the elements that collaborate in the construction of meaning and in the texture in text, focusing on referencing. This process constitutes a discursive activity carried out through the construction and reconstruction of objects of discourse, carried out by individuals in a process of interaction, which means that it carries, among other factors, the interests and views of interlocutors involved in speech (KOCH; ELIAS, 2006). For a refined understanding of the corpus, considering the limits and possibilities of this research, we decided to emphasize, among the possible elements for referencing in Portuguese, the non-coreferential retrieval operations, since they are conceived as a form of manifestation of the text producer (KOCH, 2005). We assume that the approach of this language resource in the teaching of Portuguese can help students in textual interpretation, in view of its role in the process of extracting relevant information from text. Aiming at diagnosing the use of referencing strategies, we analyze answers for comprehension questions of students from the 5th grade of a public school in Cascavel (Paraná, Brazil). Firstly, we examine the students interpretation of two versions of the fable The fox and the grapes, without a previous approach of the linguistic strategy proposed. Secondly, we examine the students interpretation of two versions of the fable The wolf and the lamb, after approaching non-coreferential anaphora. We found that, by using this kind of anaphora in their responses, students evinced their choices for highlighting features or characteristics of the referent, and thus evaluate it according to their beliefs and views. We found that students used strategies to reconstruct the referent, demonstrating comprehension of the texts read. We conclude that such linguistic mechanism is much more than just a retrieval resource, but it constitutes a mark and evidence of a strategy used in producing the utterance, which portrays the recategorization of objects of discourse. This process has relevant argumentative value, since the selection of certain types of non-coreferential anaphora is based on a number of discursive factors and reflects the speaker s communicative purposes. For this study, the main theoretical frameworks come from Kleiman (2009), Koch (2004, 2005, 2006, 2008, 2009), Koch and Elias (2006), Mondada and Dubois (2003), and others.